DESTILASI AIR LAUT MENGGUNAKAN PEMANAS MATAHARI DENGAN REFLEKTOR CERMIN CEKUNG - Fanrico Sanjaya Tambunan; Muhammad Edisar; Juandi M (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
A research has been done in distilling seawater using solar heater with and without concave mirror reflector. The concave reflector mirror has been made with its diameter of 2.2 meters, height of 0.3 meters and focus of 1 meter. The reflector was placed on the ground and was directly illuminated by the sunlight. The collector which contained seawater was exactly placed on the focus of the reflektor. During the heating, thetemperature was measured every hour from 08.00 to 16.00 WIB. The observation was done for seven days. The results showed that maximum temperature of seawater using the reflector was about 100o C and 140oC at the focus and the best daily destilling volumewas 688 ml. The results distilling without reflector showed maximum temperature of seawater was about 64oC and the best daily destilling volume was 180 ml. The laboratory testing of the samples before and after distilling showed that there was significantly improvement of water quality, especially in salinity which decreased to be zero after distilling.